Management of Psycho-Physiological aspect of Bronchial Asthma through Yogic Intervention - SARITA PRAJAPATI; RAKESH VARMA; AMAL K. DUTTA (Dr. Chinmay Pandya, 2014)
In this study eighty bronchial asthma patients were selected through accidental sampling and sample was divided into experimental group (n=40) and control group (n=40). They underwent Yoga therapy program for 60 days with an integrated set of yogic practices, including jihvamula, karnarandhra, kapalrandhra, tadasana, tiryaka tadasana, kati chakrasana and marjariasana , nadishodhan pranayama, bhastrika pranayama and Gayatri mantra. Bronchial asthmatics practiced these exercises for 45 minutes daily for 60 days. Stress level and forced expiratory volume in one second (FEV1) were assessed on all the Bronchial asthmatics, both initially and after completion of study. The obtained data were statistically analyzed through paired t-test. Subjects of experimental group showed a statistically significant decreasing trend in average stress level and increasing trend in average forced expiratory volume in one second (FEV1) after 60 days Yoga practice, while control group showed no such improvement (P>0.01).